Effect of dietary supplementation of yeast culture Saccharomyces cerevisiae in lactating female goats - Zhang, Li; Qin, Ge; Guo, Jiaxue; Zhang, Mingding; E, Guangxin; Huang, Yongfu; Han, Yanguo (Frontiers in Veterinary Science, 2024)
This study was designed to investigate the effects of adding a novel yeast culture, Saccharomyces cerevisiae refermented sorghum distiller's dried grains with solubles (SSDDGS), to the diets of lactating female goats on lactation performance and lamb growth performance. We divided 10 lactating Dazu black goats of similar age, weight, and offspring into two groups: one fed a pelleted diet with 50 g/day SSDDGS (ET), and the other without SSDDGS as a control (EC) for 7 weeks. We monitor the weight changes of each goat and collect blood and milk samples from experimental ewes at specific times for hormone and milk composition determination. We use ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) to detect metabolites in the serum of lactating ewes. Our results showed that SSDDGS supplementation significantly reduced female goats' average daily weight loss during weeks 2–4 of lactation and increased serum IGF-1 and prolactin levels at week 4 (p < 0.05). SSDDGS supplementation in early lactation significantly increased milk protein, lactose, and ash content (p < 0.05). UPLC-MS/MS analysis showed that SSDDGS changed the levels of 58 metabolites in the serum of lactating goats. These metabolites were mainly involved in the sohingolipid signaling pathway, and cysteine, methionine, and sphingolipid metabolism. In summary, Yeast culture SSDDGS reduced weight loss, enhanced milk quality, and modified metabolic profiles in early lactation goats, providing insight into the potential regulatory role and mechanism of yeast culture in lactation female goats.